Effect of far-red light on the production and diversity of ginsenosides in leaves of Panax ginseng Meyer - Padmanaban Mohanan; Tae-Jin Yang; Young Hun Song (Applied Biological Chemistry, 2023)
Abstract Ginsenosides are the most valuable and pharmacologically active triterpenoid saponins found in Panax ginseng. Although light quality affects ginsenoside content, little is known about the underlying genetic and regulatory mechanisms. Additionally, the correlation between the adaptability of ginseng to shade and ginsenoside biosynthesis remains poorly understood. In the present study, transcriptome analysis of ginseng seedlings using RNA sequencing revealed that the expression of ginsenoside biosynthesis genes, including PgHMGR, PgFPS, PgSS, and PgUGT, was enhanced in shade conditions but downregulated by red light, indicating that far-red light might play an essential role in ginsenoside production. Further, gene expression analysis in adventitious roots and 2-year-old plants using qRT-PCR showed that the light quality-mediated expression patterns of ginsenoside genes varied with tissue and age. However, unlike the transcriptome, there was no difference in the total ginsenoside content in seedlings among various light conditions. Nevertheless, the amount of major protopanaxadiol-type ginsenosides increased under shade and red light conditions. Unlike seedlings and adventitious roots, there was a decrease in the expression of PgHMGR, PgFPS, PgSS, and PgDDS in 2-year-old plants, along with an increase in the ginsenoside content, under far-red light. Taken together, our findings suggest that far-red light is an important environmental factor for ginsenoside biosynthesis and diversification and provide information that can improve the quality of ginseng produced for medicinal purposes.